Pair fidelity in long-lived parrots: genetic and behavioural evidence from the Crimson Rosella (Platycercus elegans). (2nd October 2018) - Eastwood, Justin R.; Berg, Mathew L.; Ribot, Raoul F. H.; Stokes, Helena S.; Martens, Johanne M.; Buchanan, Katherine L.; Walder, Ken; Bennett, Andrew T. D.
ABSTRACT: Genetic analyses have revolutionised our understanding of avian mating systems. However, the majority of such studies to date have focused on passerine species. Despite this taxonomic bias, extra-pair paternity (EPP) and conspecific brood parasitism (CBP) are usually concluded to be less common in taxa with pronounced longevity, socially monogamous mating systems, and bi-parental care. The order Psittaciformes, with around 350 species worldwide, has long-lived species that are relatively under-studied with respect to parentage and pair fidelity. Although studies have revealed a variety of mating systems in Psittaciformes, there is little work testing whether EPP or CBP occur in Psittaciformes. To test for genetic and social pair fidelity we studied an Australian parrot, the Crimson Rosella ( Platycercus elegans ), over 8 years at three sites in south-eastern Australia. Using nine microsatellite markers in 42 pairs and their offspring, we found no cases of EPP. However, we found one case of CBP, suggesting that P. elegans females do adopt alternative breeding strategies, albeit at low levels. We also show that over the 8 years of study 32% of recaptured individuals paired with more than one partner in different years. Our results are consistent with assumption of low EPP in parrots, but challenge the notion that this is associated with long-term pair bonds.